Methylene blue dosing strategies in critically ill adults with shock—A retrospective cohort study - Sari-Yavuz, Sibel; Heck-Swain, Ka-Lin; Keller, Marius; Magunia, Harry; Feng, You-Shan; Haeberle, Helene A.; Wied, Petra; Schlensak, Christian; Rosenberger, Peter; Koeppen, Michael (Frontiers in Medicine, 2022)
Abstract Background: Shock increases mortality in the critically ill and the mainstay of therapy is the administration of vasopressor agents to achieve hemodynamic targets. In the past, studies have found that the NO-pathway antagonist methylene blue improves hemodynamics. However, the optimal dosing strategy remains elusive. Therefore, we investigated the hemodynamic and ICU outcome parameters of three different dosing strategies for methylene blue. Methods: We performed a retrospective cohort study of patients in shock treated with methylene blue. Shock was defined as norepinephrine dose > 0.1 µg/kg/min and serum lactate level > 2 mmol/l at the start of methylene blue administration. Different demographic variables, ICU treatment, and outcome parameters were evaluated. To compare the differences in the administration of vasopressors or inotropes, the vasoactive inotropic score (VIS) was calculated at different time points after starting the administration of methylene blue. Response to methylene blue or mortality at 28 days were assessed. Results: 262 patients from July 2014 to October 2019 received methylene blue. 209 patients met the inclusion criteria. Three different dosing strategies were identified: bolus injection followed by continuous infusion (n=111), bolus injection only (no continuous infusion; n=59) or continuous infusion only (no bolus prior; n=39). The groups did not differ in demographics, ICU scoring system, or comorbidities. In all groups, VIS decreased over time, indicating improved hemodynamics. Cardiogenic shock and higher doses of norepinephrine increased the chance of responding to methylene blue, while bolus only decreased the chance of responding to methylene blue treatment. 28-day mortality increased with higher SAPSII scores and higher serum lactate levels, while bolus injection followed by continuous infusion decreased 28-day mortality. No severe side effects were noted Conclusions: In this cohort, methylene blue as a bolus injection followed by continuous infusion was associated with a reduced 28-day mortality in patients with shock. Prospective studies are needed to systematically evaluate the role of methylene blue in the treatment of shock.